Character in The Kurdish Drama as an Example - Semo, Ibrahim A. (Humanities Journal of University of Zakho, 2013)
This research entitled "character in the Kurdish drama as an example" deals with character, its definition, the way of its creation and its development. Furthermore , it tackles types of character in accordance with theorists’ points of view who divided literary characters into two types: major characters and secondary character. Of the most important topics of this study is the way of creating characters on the part of the writer. In the dramatic text’’ written by Ahmed Salar, the social , psychological , and physical aspects in addition to authenticity, hope, abandening hope, soliloquy, monologue, etc. have been analyzed. The study has concluded that the writer, in this dramatic text, has been able to point out the character’s role by a scientific and technical way in addition to pointing out the writers’ harmony, consciousness and views of the conditions in which they live.